Non-pharmacological therapies for postviral syndromes, including Long COVID: a systematic review and meta-analysis protocol. Issue 4 (11th April 2022) - Chandan, Joht Singh; Brown, Kirsty; Simms-Williams, Nikita; Camaradou, Jenny; Bashir, Nasir; Heining, Dominic; Aiyegbusi, Olalekan Lee; Turner, Grace; Cruz Rivera, Samantha; Hotham, Richard; Nirantharakumar, Krishnarajah; Sivan, Manoj; et al.
Abstract : Introduction: Postviral syndromes (PVS) describe the sustained presence of symptoms following an acute viral infection, for months or even years. Exposure to the SARS-CoV-2 virus and subsequent development of COVID-19 has shown to have similar effects with individuals continuing to exhibit symptoms for greater than 12 weeks. The sustained presence of symptoms is variably referred to as 'post COVID-19 syndrome', 'post-COVID condition' or more commonly 'Long COVID'. Knowledge of the long-term health impacts and treatments for Long COVID are evolving. To minimise overlap with existing work in the field exploring treatments of Long COVID, we have only chosen to focus on non-pharmacological treatments. Aims: This review aims to summarise the effectiveness of non-pharmacological treatments for PVS, including Long COVID. A secondary aim is to summarise the symptoms and health impacts associated with PVS in individuals recruited to treatment studies. Methods and analysis: Primary electronic searches will be performed in bibliographic databases including: Embase, MEDLINE, PyscINFO, CINAHL and MedRxiv from 1 January 2001 to 29 October 2021. At least two independent reviewers will screen each study for inclusion and data will be extracted from all eligible studies onto a data extraction form. The quality of all included studies will be assessed using Cochrane risk of bias tools and the Newcastle-Ottawa grading system. Non-pharmacological treatments for PVS and Long COVID will be narratively summarised and effect estimates will be pooled using random effects meta-analysis where there is sufficient methodological homogeneity. The symptoms and health impacts reported in the included studies on non-pharmacological interventions will be extracted and narratively reported. Ethics and dissemination: This systematic review does not require ethical approval. The findings from this study will be submitted for peer-reviewed publication, shared at conference presentations and disseminated to both clinical and patient groups. PROSPERO registration number: The review will adhere to this protocol which has also been registered with PROSPERO (CRD42021282074).